2015
DOI: 10.1115/1.4031938
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Cemented Femoral Prosthesis Considering Bone Remodeling

Abstract: The study presents a numerical methodology for minimizing the bone loss in human femur submitted to total hip replacement (THR) procedure with focus on cemented femoral stem. Three-dimensional computational models were used to describe the femoral bone behavior. An optimization procedure using the genetic algorithm (GA) method was applied in order to minimize the bone loss, considering the geometry and the material of the prosthesis as well as the design of the stem. Internal and external bone remodeling were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As the implant material significantly affects the transmission of stress from the implant to the surrounding bone, it is essential to evaluate the bone remodelling rate and related failure index characteristics for hip implants made from various materials. The predominant bone remodelling estimating model, 48,[90][91][92][93] proposed by Winan et al 94 and Huiskes et al, 95 is based on the strain energy density (SED), which is widely used (J cm À3 ). The bone remodelling rate Dr Dt can be estimated using the following eqn (21).…”
Section: Porous and Lattice Structurementioning
confidence: 99%
See 2 more Smart Citations
“…As the implant material significantly affects the transmission of stress from the implant to the surrounding bone, it is essential to evaluate the bone remodelling rate and related failure index characteristics for hip implants made from various materials. The predominant bone remodelling estimating model, 48,[90][91][92][93] proposed by Winan et al 94 and Huiskes et al, 95 is based on the strain energy density (SED), which is widely used (J cm À3 ). The bone remodelling rate Dr Dt can be estimated using the following eqn (21).…”
Section: Porous and Lattice Structurementioning
confidence: 99%
“…The bone remodelling rate Dr Dt can be estimated using the following eqn (21). 42,48,[90][91][92][93] Fig. 6 Indication of Gruen Areas in (a) intact femur and (b) implanted femur.…”
Section: Porous and Lattice Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, studies have shown benefits of applying optimization in biomechanical situations [19,20]. For this, it is important that adequate mathematical models are applied, as it may require a high computational cost.…”
Section: Introductionmentioning
confidence: 99%